Revisiting teacher commitment: A bibliometric analysis based on CNKI and Scopus databases - Yang Shao; Sabariah Binti Shariff; Connie Cassy Ompok (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2025)
The development of teacher commitment is crucial for improving educational quality and teacher retention. This study aimed to understand the current research on teacher commitment and predict future trends by analyzing literature from the CNKI and Scopus databases. A total of 302 and 647 relevant articles were selected. High- frequency keyword and co-word analysis revealed that "organizational commitment" and "teacher commitment" were the most common keywords in both databases. Other prominent themes included job satisfaction and leadership in Scopus, and career commitment and teacher turnover in CNKI. The findings highlight the importance of workplace factors and regional differences in teacher commitment research, providing insights for future studies.